1997
DOI: 10.1111/1467-9914.00043
|View full text |Cite
|
Sign up to set email alerts
|

Remitting Behaviour of “Temporary” and “Permanent” Migrants: The Case of Greeks in Germany and Australia

Abstract: This paper makes the point that migrants have different motives for sending remittances and remittance receivers have different claims on migrants' income, depending on whether people move to accumulate capital to improve their living at home after they return -temporary migration -or to start a new life in a foreign country -permanent migration. This hypothesis is empirically tested with data from Greek-German and Greek-Australian migration. The findings attest to the fact that German remittances constitute o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 3 publications
2
57
1
2
Order By: Relevance
“…it x is a row vector of explanatory variables excluding the lagged dependent variable with the dimension k where 1 kn  and n is the number of exogenous variables. , i t l R  is included as an explanatory variable so as to capture the theoretical conviction of dynamic effects of remittance inflows which suggests that migrant remittances could either decay or decrease in value overtime, often by the second-generation as family and social ties become weak (Lucas and Stark, 1985;Merkle and Zimmermann, 1992;Glytsos, 1997 Ex   Equation (9) also shows that there are 2 T  orthogonality restrictions in levels which are exploited; hence observation t in levels was used for the estimation, where differences are used as valid instruments, as it is assumed that x is at least predetermined.…”
Section: Empirical Model and Methodological Approachmentioning
confidence: 99%
“…it x is a row vector of explanatory variables excluding the lagged dependent variable with the dimension k where 1 kn  and n is the number of exogenous variables. , i t l R  is included as an explanatory variable so as to capture the theoretical conviction of dynamic effects of remittance inflows which suggests that migrant remittances could either decay or decrease in value overtime, often by the second-generation as family and social ties become weak (Lucas and Stark, 1985;Merkle and Zimmermann, 1992;Glytsos, 1997 Ex   Equation (9) also shows that there are 2 T  orthogonality restrictions in levels which are exploited; hence observation t in levels was used for the estimation, where differences are used as valid instruments, as it is assumed that x is at least predetermined.…”
Section: Empirical Model and Methodological Approachmentioning
confidence: 99%
“…The motive of migrants to remit also crucially depends on whether migration is temporary or permanent. For temporary migrants, remittances are often obligatory, while remittances send by permanent migrants are gifts to relatives in the home country (Glytsos, 1997). Agarwal and Horowitz (2002) recently tested altruism versus risk sharing motives to remit and gave evidence supporting the altruistic incentive.…”
Section: Empirical Literaturementioning
confidence: 99%
“…In a survey of Tongan migrants in New Zealand, Gibson and colleagues (2006) find that remittances sent would rise by 0.22 percent if costs fell by 1 percent. Other studies have found that remittances are influenced by interest rate differentials, exchange rate premia (the difference between the official and black market exchange rates), and the duration of migration (Glytsos 1997;ElSakka and McNabb 1999). Freund and Spatafora (2008) report that recorded remittances depend negatively on transfer costs and the parallel market premium, as migrants may prefer to send money through informal channels when transfer costs are high or when the official exchange rate is unattractive.…”
Section: Determinants Of Remittancesmentioning
confidence: 99%
“…Several studies have documented that that remittance respond positively to an increase in the host country GDP (Glytsos 1997, Silva andHuang 2006;Frankel 2009;Ruiz and Vargas-Silva 2010), and in a negative or counter-cyclical manner during economic downturns, financial crises and natural disasters in the migrant-sending country (Clarke and Wallsten 2004;World Bank 2005;Yang and Choi 2007;Yang 2008;Frankel 2009;Mohapatra et al 2009;Ratha 2010). 3 In terms of the relative importance of home and host country factors, several studies have found that the host country economic conditions appears to be more important compared to home country factors (Swamy 1981;Glytsos 1997;Silva and Huang 2006;Barajas et al 2010).…”
Section: Determinants Of Remittancesmentioning
confidence: 99%